PENGARUH KECUKUPAN MODAL, LIKUIDITAS, NET INTEREST MARGIN DAN PERPUTARAN KAS TERHADAP PROFITABILITAS PADA LPD DI KECAMATAN ABIANSEMAL - Edi Hendiartha, I Gusti Ngurah; Suarjaya, A. A. Gede (E-Jurnal Manajemen, 2015)
Lembaga Perkreditan Desa (LPD) is a non-bank financial institutions which raise public funds in the form of savings and channeling village back in the form of credit. The main products of LPD offered to clients is savings, deposits and working capital loans. To maintain and improve kontuinitasnya, LPD also requires good financial performance to improve profitability LPD. This study aims to prove the effect of capital adequacy, liquidity, net interest margin and cash turnover on profitability. The sample in this study is the entire LPD in the district Abiansemal 2009-2013 period. The method used is multiple linear regression. This study proves that the capital adequacy, liquidity and net interest margin partially positive and significant impact on the profitability of LPD in kecamatatan Abiansemal, while cash turnover no significant effect on the profitability of LPD in kecamatatan Abiansemal. The implications of this research is in the district Abiansemal LPD shall make cash turnover in LPD faster in order to increase profitability.
Keywords: capital adequacy, liquidity, net interest margins, cash turnover, liquidity